2011
DOI: 10.1007/s13239-011-0063-5
|View full text |Cite
|
Sign up to set email alerts
|

Pre-clinical Implants of the Levitronix PediVAS® Pediatric Ventricular Assist Device: Strategy for Regulatory Approval

Abstract: The PediVAS blood pump is a magnetically levitated centrifugal pump designed for pediatric bridge-to-decision or bridge-to-recovery in pediatric patients from 3–20kg in weight. In preparation for submission of an investigational device exemption (IDE) application, we completed a final six-animal series of pre-clinical studies. The studies were conducted under controlled conditions as prescribed by the recently released FDA guidance document for animal studies for cardiovascular devices. Three 30-day chronic le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, it is misleading to extrapolate that a lower pump flow leads to less blood damage [10,15]. To date, there are only a few pumps that have been designed for these requirements or tested in the low-flow range [16][17][18][19]. This highlights the urgent need to focus on technical implications associated with the use of current centrifugal blood pumps in different low-flow ranges.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is misleading to extrapolate that a lower pump flow leads to less blood damage [10,15]. To date, there are only a few pumps that have been designed for these requirements or tested in the low-flow range [16][17][18][19]. This highlights the urgent need to focus on technical implications associated with the use of current centrifugal blood pumps in different low-flow ranges.…”
Section: Introductionmentioning
confidence: 99%
“…Such observations have been reported for other investigational devices in ovine models. 8,11,18 The histopathologic findings suggested that these infarctions were well-healed, and occurred early in the post-operative period. A potential cause may have been heightened inflammatory response and platelet activation, such as evidenced by elevated and variable neutrophil counts in PF2.2 from a confirmed fecal culture for whipworm.…”
Section: Discussionmentioning
confidence: 96%